A Mahabbah Love Rabiah Al Adawiyah's Discourse (Paul Ricoeur's Hermeneutic Study) - Anggra Agastyassa Owie (Jurnal Mediakita : Jurnal Komunikasi dan Penyiaran Islam, 2022)
Da'wah is transcendental communication in doing good. Prophetic communication in da'wah communication shows that later a communicator or what is commonly called a preacher in da'wah communication will convey divine messages to the honeymooners/congregations or communicants. The three pillars as the characteristics of prophetic social science are amar ma'ruf (humanization), nahi munkar (liberation), and faith in Allah (transcendence). Hermeneutics has a foundation for understanding the birth of a text in a certain context or how a context gives rise to certain texts. In this study using qualitative methods with literature studies using paul ricoeur's hermeneutic analysis. The result of this research is that in Rabiah Al-Adawiyah's Mahabbah love poem, everyone's life will experience suffering. Rabiah's poem contains the prophetic values of amar ma'ruf (humanization), nahi munkar (liberation), and faith in Allah (transcendence). In the context of da'wah communication, Rabiah Al Adawiyah is a communicator. The source of communication that Rabiah took was from the upbringing she received. The communication messages conveyed by Rabiah aim for us to always worship and prioritize Allah. The da'wah medium used is the poetry delivered by Rabih in the book Mahabbah Cinta Rabiah Al Adawiyah, Jamaah or honey or communicants who receive the message are us, the readers of this book. The purpose of the activities carried out is to invite people like Rabiah who they are devoted to worship and really love Allah as their Lord. The feedback generated in this communication process is in a positive direction where no reader has expressed dissatisfaction with the writing in this book.